DOA NABI INGIN KAYA DAN INGIN MISKIN - Mahfud, Muhammad (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
Prayer is a communication tool of human to the God. One of popular prayer in the community is related to the ProphetÃ¢â‚¬â„¢s asking to be a poor man, and in the other side the asking to be a rich man. This article discusses the contradiction of the ProphetÃ¢â‚¬â„¢s prayer to be a poor man, and in the other side the prayer to be a rich man through TakhrÃ„Â«j al-Ã¡Â¸Â¤adÃ„Â«th method. The ProphetÃ¢â‚¬â„¢s prayers give understanding that the followers should not live with their wealth; however, poor here means simplicity. In other side, the both hadith are Ã¡Â¸ÂaÃ¢â‚¬â„¢Ã„Â«f. Keywords: rich, poor, TakhrÃ„Â«j al-Ã¡Â¸Â¤adÃ„Â«th, makna Ã¡Â¸Â¥adÃ„Â«th